Characteristics of Teaching Theoretical Foundations of Informatics in the System of Pedagogical Higher Education - Ilyasova Zuhra Kenesbaevna (International Journal on Integrated Education, 2021)
The article describes the methodology of teaching the subject of the theoretical foundations of computer science in the credit-modular system in the system of pedagogical higher education. It also defines the requirements and objectives in relation to knowledge, skills and competencies that students must acquire in mastering the subject.